Pengembangan Platform Hands-on Lab untuk Manajemen Identitas dan Akses menggunakan Teknologi Virtualisasi berbasis Container - Fabiansyah Raam Pontoh; Achmad Basuki; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Hands-on Lab is a lab that is used to provide an environment that is able to provide learners with practical experiences. Providing a hands-on lab environment for practical deepening of understanding of the Identity and Access Management coursework requires a virtualized computing and networking environment that can separate resources for each learner. The choice of platform and technology for computing and virtual networks is necessary for the effectiveness of activities in the hands-on lab. This final project implements a hands-on lab with container-based virtualization technology. The container was chosen because of the characteristics of being lightweight and fast to build. The developed hands-on lab also needs to have an automated assessment system so that it can be used independently by learners. The implementation of the hands-on lab platform in this final project requires two main components, namely: a website lab and a hands-on lab server. The website lab is used for interaction between learner and the hands-on lab server, then the hands-on lab server is used as a place for the hands-on lab container to run. The main components of the hands-on lab of identity and access management in this final project consist of six software that has these functions: managing identity and access management, managing databases, testing web, performing LDAP access, sharing container's terminal, and as a proxy for sharing container's terminal. Communication of the lab website and hands-on lab server for container management is done through Secure Shell. Learners access to hands-on lab learning activities using a terminal container that is shared from the hands-on lab server to the lab website. The results of the implementation based on the functional testing aspect show that the hands-on lab can run according to its function in providing containers, stopping containers, and conducting automatic assessments according to the needs of learning materials. Non-functional tests will also be performed to calculate hands-on lab behavior when performing automated assessments, running, and stopping containers. In addition, testing is also carried out to determine the resource utilization required by a hands-on lab. The non-functional test results show that time behavior is quite responsive and resource utilization is quite good with 1.03% CPU and 13.78% RAM utilization.